PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP BUDAYA ORGANISASI DAN KINERJA KARYAWAN PADA PT RESOURCE EQUIPMENT INDONESIA DI BALIKPAPAN - Alisa Alaina; Sukisno S Riadi; Fitriadi Fitriadi (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2020)
The purpose of this study was to analyze the influence of leadership on organizational culture, to analyze the effect of motivation on organizational culture, to analyze leadership on organizational culture and employee performance, to analyze motivation for organizational culture and the performance of employees of PT Resource Equipment Indonesia in Balikpapan.In order to test the hypothesis the author uses Path analysis tool supporting program of SPSS 21. The population in this study were employees of PT Resource Equipment Indonesia in Balikpapan, which amounted to 40 employees. Based on the results of the study obtained an equation consisting of the following equation:-          the first substructure, Y1 = 0.147 X1 + 0.641 X2  -          the second substructure, Y2 = -0.049 X1 + 0.565 X2 + 0.150 Y1The results of the study indicate that; 1) Leadership has a positive but not significant effect on organizational culture. 2) Motivation has a positive but not significant effect on organizational culture. 3) Leadership does not have a positive effect and is not significant on Employee Performance. 4) motivation has a significant positive influence on employee performance. 5) Organizational culture has a significant positive influence on employee performance. 6) Leadership and organizational culture do not affect employee performance. 7) Motivation and organizational culture influence employee performance.